Using Genetic Algorithms to Design an Optimized Keyboard Layout for Brazilian Portuguese - Pacheco, Gustavo; Palmeira, Eduardo; Yamanaka, Keiji (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2020)
Currently, keyboards are the most common means of communicating with computers. Despite being the most commonly used keyboard layout, QWERTY has had various issues raised concerning its effectiveness, as it is not efficient in English (target language) or in fact other languages. Therefore, this paper presents the development process of a Genetic Algorithm with the intention of generating a more adequate and coherent layout proposal for Brazilian Portuguese, which has its focus on ergonomics and user productivity. Using five ergonomic criteria and a statistical analysis of the characters and sequences of most frequently used pairs in Brazilian Portuguese, a layout approximately 53% better than QWERTY was obtained.